The Climate Security Inequality Nexus: A critical analysis of pathways and synergies - Dutta Gupta, Tanaya; Schapendonk, Frans; Suza, Ma; Phuong Le, Dung; Läderach, Peter R.D.; Pacillo, Grazia (2021)
Inequality is a key component of any crisis, whether it is related to climate, conflict, or a global pandemic, as it can reveal why some people and regions are disproportionately impacted over others. While interaction of climate impacts with structural inequalities can exacerbate already existing risks of insecurity and fragility, it can also leave room for institutions and interventions to address unequal power relations between actors and find paths for social cohesion and peace. Focusing on the central role of inequality as a driver, an outcome, and an intermediary variable in the climate-security-inequality nexus, this paper attempts to connect dots that have remained relatively underexamined in existing discourse. Bringing multi-disciplinary literature on inequality-conflict and inequality-climate linkages in conversation, the paper seeks to unpack interrelated pathways through which inequality-related resource, livelihood and food insecurities can translate to conflict risks. Using the case of how and to what extent CGIAR publications on land, water, and food systems have engaged with this nexus, it further aims to highlight advances and gaps in synergistic understanding of relationships between climate-fragility risks, resilience, and peace. The paper relies on the following methods: 1) a review of academic and grey literature, and 2) co-occurrence analysis of keywords extracted from a corpus of 14,675 publications from CGIAR’s Global Agricultural Research Data Innovation Acceleration Network (GARDIAN). Key findings emerging from the review and co-occurrence analysis support that while inequality has typically been studied in relation to either climate or conflict, there is greater scope for examining context-specific mechanisms through which inequalities at the intersection of gender, age, ethnicity, income, tenure, region, and more, may shape and be shaped by climate related security risks. Therefore, any effort to enhance resilience of climate vulnerable communities and build peace must also involve seeing and acting through the lens of inequality.